Right ventricular involvement and conduction disturbances in acute inferior wall myocardial infarction patients and their angiographic correlation - Misra, Amitava; Choudhury, Sankar Paul (International Journal of Research in Medical Sciences, 2021)
Background: Right ventricular myocardial infarction (RVMI) in the setting of inferior wall myocardial infarction (IWMI) is associated with adverse events. The study aimed to evaluate right ventricular (RV) systolic function in the first episode of IWMI by echocardiography; determine incidence of different conduction abnormalities during hospitalization in IWMI patients with and without RVMI; and determine association of these parameters with the location of significant lesion in the infarct related artery. Methods: This was a prospective study conducted from March 2014 to February 2015. Patients diagnosed with a first episode of acute ST-segment elevation IWMI who presented within 12 hours of symptom onset participated in the study. Patients were divided into two groups according to location of myocardial infarction based on electrocardiographic (ECG) findings. Four echocardiographic parameters of RV systolic function: tricuspid annular plane systolic excursion (TAPSE); systolic excursion velocity of lateral tricuspid annulus (S’); myocardial performance index by pulsed Doppler method (MPI-PD); and right ventricular fraction area change (RV-FAC) were measured. Results: Clinical presentation such as Kussmaul sign (<0.05), hypotension (<0.05), and raised jugular venous pressure (<0.05) were higher in the IWMI+RVMI group than the IWMI group. ECG-based criteria, ST elevation in V4R to predict RVMI revealed 78.84% sensitivity, 88.86% and 87.46% positive predictive value (p<0.05). TAPSE (13.44±1.46 versus 21.0±1.16 mm, p<0.05), S’ (9.03±1.51 versus 16.26±1.21 cm/sec, p<0.05) and RV-FAC (31.24±3.15 versus 47.17±3.65%, p<0.05) were lower in the IWMI+RVMI group compared to the IWMI group. Conclusions: Cut-off values of TAPSE, S’, MPI-PD, and RV-FAC have high sensitivity and specificity for predicting proximal right coronary artery lesions.